2014
DOI: 10.1186/s12917-014-0221-8
|View full text |Cite
|
Sign up to set email alerts
|

The presence of six potentially pathogenic viruses in pigs suffering from post-weaning multisystemic wasting syndrome

Abstract: BackgroundPorcine circovirus type 2 (PCV2) is an etiological agent of porcine circovirus diseases (PCVDs). Post-weaning multisystemic wasting syndrome (PMWS) as the most important PCVD is considered a multifactorial disease. It was demonstrated that not only PCV2 but several viruses are associated with PMWS. Studies of viral co-infections in PMWS pigs led often to controversial results. The aim of this work was to determine the presence of emerging (PRRSV), re-emerging (PTV) and newly-emerging (TTSuV1, TTSuV2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 47 publications
2
26
1
Order By: Relevance
“…Nevertheless, Brazil (Teixeira et al., ), Cuba (Pérez et al., ) and Japan (Taira et al., ) showed prevalence values of 48%, 40% and 30%, respectively. Conversely, the data regarding TTSUV1b are even more contrasting, as Spain has reported a frequency of 91% (Kekarainen et al., ; Nieto et al., ) to 100% (Aramouni et al., ), consistent with the 94% reported in Sweden (Blömstrom et al., ) and 64% found in Great Britain (McMenamy et al., ) and Slovakia (Vlasakova et al., ). Such prevalence is considerably dissimilar to that found in a Mexican retrospective study in which lower frequencies of both Iotatorquevirus species than shown in other reports were found.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, Brazil (Teixeira et al., ), Cuba (Pérez et al., ) and Japan (Taira et al., ) showed prevalence values of 48%, 40% and 30%, respectively. Conversely, the data regarding TTSUV1b are even more contrasting, as Spain has reported a frequency of 91% (Kekarainen et al., ; Nieto et al., ) to 100% (Aramouni et al., ), consistent with the 94% reported in Sweden (Blömstrom et al., ) and 64% found in Great Britain (McMenamy et al., ) and Slovakia (Vlasakova et al., ). Such prevalence is considerably dissimilar to that found in a Mexican retrospective study in which lower frequencies of both Iotatorquevirus species than shown in other reports were found.…”
Section: Introductionmentioning
confidence: 78%
“…Additionally, porcine dermatitis and nephropathy syndrome (PDNS) was reproduced in PCV2‐negative pigs previously inoculated with TTSuV1a and porcine respiratory and reproductive syndrome virus (PRRSv; Krakowka & Ellis, ). In Europe, the TTSuV1a DNA prevalence has been high in serum, being 66%–76% in Spain (Kekarainen et al., ; Aramouni et al., ; Aramouni, Kekarainen, Ganges, Tarradas, & Segalés, ; Nieto, Aramouni, Grau‐Roma, Segalés, & Kekarainen, ), 77% in Sweden (Blömstrom et al., ) and 71.4% in Slovakia (Vlasakova, Leskova, Sliz, Jackova, & Vilcek, ), while in TTSuV1a, prevalence in fresh tissue samples was 41%–48% in Great Britain (McMenamy et al., ). Nevertheless, Brazil (Teixeira et al., ), Cuba (Pérez et al., ) and Japan (Taira et al., ) showed prevalence values of 48%, 40% and 30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…of their genetic background (Opriessnig et al, 2008). Moreover, the fact that PCV2 needs one or more co-factors for the development of PCV2-SD (Lohse et al, 2008) make etiopathogenesis of PCV2 related diseases even more complex than previously assumed (Magar et al, 2000, Savić et al, 2010, Vlasakova et al, 2014.…”
Section: Introductionmentioning
confidence: 78%
“…However, this virulent manifestation is now considered rare and only milder forms of neurologic disease associated with PTV-1 or other PTV serotypes have been reported in growing pigs in Canada, Spain and Brazil during the last years [2,5,8]. Although co-infections were not detected in these cases, immunosuppressive pathogens, such as porcine circovirus type 2 (PCV-2) and/or porcine reproductive and respiratory syndrome virus (PRRSV) could predispose animals to develop neurologic PTV disease [3,18]. It is therefore important to screen for immunosuppressive pathogens when PTV is suspected to be associated with neurologic signs.…”
Section: Introductionmentioning
confidence: 99%